2021
DOI: 10.3390/ani11030612
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Behavioural Effects of Individual versus Pair Housing of Calves at Different Ages on a UK Commercial Dairy Farm

Abstract: Housing management of dairy calves is one of the factors that contributes to a successful rearing outcome. Individual housing of pre-weaned calves is thought to provide enhanced biosecurity and easier monitoring of the individual, and so remains prevalent in the UK. Behavioural studies have, however, found that pair housing is important for social learning, with positive impacts on health and welfare. This study utilised a single UK commercial dairy farm to establish if individual housing, pair housing from bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
2
13
0
2
Order By: Relevance
“…With regard to influence of age at grouping on concentrate intake, Costa et al (2015) found that calves paired at 6 days of age consumed more concentrate (in the period from 3 to 10 weeks) than calves paired at the age of 6 weeks and individually housed, which suggests that early social housing, and thus early social facilitation of concentrate intake, is important for later concentrate intake. Mahendran et al (2021) saw a higher concentrate intake in paired calves compared with individually housed animals, but no difference between calves paired days after birth and paired at 21 days old. These results are in line with outcomes from a study that found no difference in concentrate intake (measured at 3-7 weeks) between calves paired within 3 days of birth and at 14 days old (Jensen and Larsen, 2014), or between calves paired within 3 days of birth and at 21 days old .…”
Section: Is Group Housing Of Young Calves Beneficial Compared With In...mentioning
confidence: 80%
See 1 more Smart Citation
“…With regard to influence of age at grouping on concentrate intake, Costa et al (2015) found that calves paired at 6 days of age consumed more concentrate (in the period from 3 to 10 weeks) than calves paired at the age of 6 weeks and individually housed, which suggests that early social housing, and thus early social facilitation of concentrate intake, is important for later concentrate intake. Mahendran et al (2021) saw a higher concentrate intake in paired calves compared with individually housed animals, but no difference between calves paired days after birth and paired at 21 days old. These results are in line with outcomes from a study that found no difference in concentrate intake (measured at 3-7 weeks) between calves paired within 3 days of birth and at 14 days old (Jensen and Larsen, 2014), or between calves paired within 3 days of birth and at 21 days old .…”
Section: Is Group Housing Of Young Calves Beneficial Compared With In...mentioning
confidence: 80%
“…Mahendran et al. ( 2021 ) saw a higher concentrate intake in paired calves compared with individually housed animals, but no difference between calves paired days after birth and paired at 21 days old. These results are in line with outcomes from a study that found no difference in concentrate intake (measured at 3–7 weeks) between calves paired within 3 days of birth and at 14 days old (Jensen and Larsen, 2014 ), or between calves paired within 3 days of birth and at 21 days old (Duve and Jensen, 2012 ).…”
Section: Assessmentmentioning
confidence: 95%
“…In contrast with previous studies, only seven of the 49 18 month old experimental heifers approached and interacted with the novel object in the present study. Wagner et al ( 2015 ) observed up to 24 of their 26 post-partum experimental animals approaching a traffic cone in the indoor walkway between the milking parlour and their home barn, for instance, while at the other end of the age spectrum an umbrella at the side of their outdoor rearing pens was approached by 43 out of 58 six week old calves studied by Mahendran et al ( 2021 ). While in the present study each experimental treatment comprised a variety of dairy breeds, Mahendran et al ( 2021 ) recruited only Holsteins and Wagner et al ( 2015 ) studied both German Holsteins and German Red Pieds, with no reports of breed differences in behaviour in the latter study.…”
Section: Discussionmentioning
confidence: 99%
“…Pairing housing systems, being the current recommended practice for rearing, improves calves’ health and welfare [ 82 , 85 ]. These systems increase positive social behavior, promoting the intake of solid feed, higher average daily gain, and reducing fearfulness of animals [ 86 , 87 ]. Rearing calves even in groups from a very young age is now being considered, since this practice allows for less labor, distress, and the adoption of new feeding technologies [ 88 ].…”
Section: Milk Production: From Rearing To Milkingmentioning
confidence: 99%